Case Report: A rare case of complex Behçet’s disease complicated with acute tubular necrosis and IgA nephropathy, coexists with myelodysplastic syndrome, trisomy 8 and intestinal involvement - Zhang, Peipei; Zhang, Wen; Xia, Hong; Fan, Zhenliang; Fan, Junfen; Ma, Hongzhen; Zhang, Chunli; Liu, Shuyan (Frontiers in Immunology, 2025)
Behçet’s disease (BD) is a rare systemic disease in which small-vessel vasculitis impacts multiple bodily organs. It is typically marked by recurrent oral and genital ulcers, uveitis, and cutaneous lesions. However, peripheral vessels, cardiovascular structures, central nervous system, gastrointestinal tract, joints, lungs, or kidneys may be affected as well. Renal involvement, although uncommon, may manifest as proteinuria, hematuria, and varying degrees of renal insufficiency. Herein, we describe a 35-year-old man with longstanding BD, myelodysplastic syndrome (MDS), and trisomy 8. He presented with cutaneous erythema and gastrointestinal bleeding (requiring colonic resection), later developing acute renal failure. Features of both acute tubular necrosis (ATN) and IgA nephropathy appeared on subsequent biopsy. Following continuous renal replacement therapy and intravenous methylprednisolone treatment, there was gradual recovery of renal function. This scenario represents a rare and severe multisystem presentation of BD with complex comorbidities, attributing the observed kidney injury to combined insults as above. Given the persistent and multifaceted nature of BD, early recognition and targeted management of renal complications are essential to preserve functional capacity and improve patient outcomes.